Optimum parameters and kinetic analysis for hot working of a homogenized Mg–8Sn–1Al–1Zn alloy. (15th November 2015) - Cheng, Weili; Tian, Quanwei; Yu, Hui; You, Bong Sun; Wang, Hongxia
Abstract: Hot deformation behavior of a homogenized Mg–8Sn–1Al–1Zn (wt.%) (TAZ811) alloy was investigated at the temperature range of 523–673 K and the strain rate of 0.33–10 s − 1 to explore its potential as a wrought alloy. The kinetic analysis indicated that dislocation climb mechanism was likely to be an operative deformation mechanism for TAZ811 alloy. To obtain the optimum hot working parameters of the alloy, processing map consisting of a power dissipation map and an instability map was constructed. The practical processing window could be determined as T = 623–673 K and ε ˙  = 0.33–3.3 s − 1 with a peak efficiency of approximately 20% occurring at 673 K and 0.33 s − 1 . The flow instability region occurs at around the temperature of 523–598 K and stain rate of 0.33–0.66 s − 1 . In addition, dynamic recrystallization (DRX) mechanisms were analyzed with respect to its microstructure, which was consistent with the predicted results from the processing map. Graphical abstract: Highlights: The hot deformation behaviors of a homogenized TAZ811 alloy were firstly reported. The practical processing window was determined through processing-map technique. The TAZ811 alloy had the potential to be deformed at relatively high strain rate. TDRX and CDRX were the main modes in low and high temperature ranges.